2022
DOI: 10.3390/healthcare10030581
|View full text |Cite|
|
Sign up to set email alerts
|

Grounding the Body Improves Sleep Quality in Patients with Mild Alzheimer’s Disease: A Pilot Study

Abstract: Background: Grounding refers to having direct contact with the Earth, such as by walking barefoot or lying on the ground. Research has found that grounding can improve inflammation, free radical damage, blood pressure, sleep quality, pain, stress, mood, and wound healing. However, there has been no research on the effect of utilizing grounding for patients with Alzheimer’s disease (AD). Thus, in this study, we investigated the effectiveness of grounding as a non-pharmacological therapy for treating sleep distu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Going one-step further and making conductive contact with the earth -touching the surface of the planet directly with the body, even just a fingertip or a toe -grounds our electrical system and provides a host of health benefits to our electrical function. Grounding improves heart rate variability (HRV) [31], increases blood perfusion [32] decreases blood viscosity [33] support muscles contraction during exertion [34][35][36] instantaneously shifts brain wave patterns and reduces ambient stress levels [37] along with supporting deeper, more restorative sleep at night [38], improving sleep quality [39] and optimizing our body's autonomic nervous system function through vagal tone support [40].…”
Section: Electrical Grounding Of Cerebrospinal Fluidmentioning
confidence: 99%
“…Going one-step further and making conductive contact with the earth -touching the surface of the planet directly with the body, even just a fingertip or a toe -grounds our electrical system and provides a host of health benefits to our electrical function. Grounding improves heart rate variability (HRV) [31], increases blood perfusion [32] decreases blood viscosity [33] support muscles contraction during exertion [34][35][36] instantaneously shifts brain wave patterns and reduces ambient stress levels [37] along with supporting deeper, more restorative sleep at night [38], improving sleep quality [39] and optimizing our body's autonomic nervous system function through vagal tone support [40].…”
Section: Electrical Grounding Of Cerebrospinal Fluidmentioning
confidence: 99%
“…Studies evaluating grounding and sleep quality found that just grounding for 30 minutes a day significantly improved sleep quality. This was a double blinded placebo based study that found that a 30 minute session was enough to make a statistically significant improvement in quality of sleep in Alzheimers patients [22].…”
Section: Indirect Ways Grounding Supports Skin Healthmentioning
confidence: 99%
“…The authors would like to make the following corrections to the published paper [ 1 ]. Replacing the Institutional Review Board number 2019011136B0 with 201901136B0 in Section 2.1.…”
Section: Text Correctionmentioning
confidence: 99%